A lethal legacy [large type] - Graham, Heather (Graham, Heather. New York confidential., 2019)
"Douglas Island sits off the coast of New York State, its imposing cliffs warning away visitors. Still, Finn Douglas has big plans for his inheritance and the rambling manor house that dominates the landscape. He has a vision to turn the island into a resort getaway for overworked city dwellers. But when the broken body of his business partner is found at the base of the rocky escarpment, he fears it wasn't an accident. Special Agent Craig Frasier agrees to help his cousin Finn by investigating and, with psychologist Kieran Finnegan at his side, heads to the island. As Craig and Kieran delve into the history of the Douglas estate, they discover that the property comes complete with strange lore and a blood-soaked past. Something evil seems to be lurking in the caverns that run beneath the stony ground. Is there something on the island that someone is willing to kill to protect? Kieran and Craig take on a dangerous search for the truth, where one false step could send them plummeting to their deaths, and one wrong turn could bring them face-to-face with a killer." -- Amazon.